Immune status and the efficacy of radiotherapy on overall survival for patients with localized Merkel cell carcinoma: An analysis of the National Cancer Database. Issue 3 (5th May 2020) - Yusuf, Mehran B; Gaskins, Jeremy; Wall, Weston; Tennant, Paul; Bumpous, Jeffrey; Dunlap, Neal
Abstract: Background: Immunosuppressed (IS) patients with Merkel cell carcinoma (MCC) have worse outcomes compared to immunocompetent (IC) patients, and it is unclear if adjuvant radiotherapy (RT) is beneficial for these patients. We sought to determine the effect of immune status on adjuvant RT efficacy regarding overall survival (OS) for patients with localized MCC. Methods: This was an observational study of National Cancer Database (NCDB) identifying patients with stage I/II or III MCC with known immune status diagnosed from 2010 to 2014. The median follow‐up time was 29 months. OS was described using Kaplan–Meier methods and compared for subgroups by immune status and adjuvant RT using log‐rank tests, multivariable Cox regression and interaction effect testing. Results: A total of 2049 IC and 255 IS patients were included. Adjuvant RT was associated with decreased hazard of death for stage I/II MCC (HR 0.65, CI 0.54–0.78) adjusting for factors including immune status. Interaction effect testing did not demonstrate a significant difference in the effect of adjuvant RT on OS between IC and IS status in either stage I/II or III MCC (both P values > 0.05). Conclusions: In this observational study, adjuvant RT was associated with decreased hazard of death for patients with stage I/II MCC regardless of immune status. Adjuvant RT should be considered for both IS and IC patients with localized MCC.